2022
DOI: 10.3389/fmolb.2022.807418
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Hepatocellular Carcinoma Based on N6-Methylandenosine–Related lncRNAs Profiling

Abstract: HCC is one of the most common types of malignancies worldwide and the fourth-leading cause of cancer deaths. Thus, there is an urgent need to search for novel targeted therapies in HCC. 186 m6a-related lncRNAs were screened for subsequent analysis. Two distinct m6A modification clusters were identified to be associated with the overall prognosis in TCGA-LIHC based on the m6A-related lncRNAs profiling, followed by univariate Cox regression analysis. In addition, four m6A-related lncRNAs prognostic signatures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Tumor purity is inversely proportional to the ratio of infiltrating immune cells (Yin et al, 2022). The relative ratios of infiltrating immune cells in each tumor sample were analyzed using the "preprocessCore", "limma", and "e1071" packages.…”
Section: Tumor Immune Microenvironment and Gene Set Enrichment Analysismentioning
confidence: 99%
“…Tumor purity is inversely proportional to the ratio of infiltrating immune cells (Yin et al, 2022). The relative ratios of infiltrating immune cells in each tumor sample were analyzed using the "preprocessCore", "limma", and "e1071" packages.…”
Section: Tumor Immune Microenvironment and Gene Set Enrichment Analysismentioning
confidence: 99%
“…Patients with advanced metastatic and/or recurrent HCCs have failed to gain benefit over the long term from standard HCC treatments such as surgical resection and liver transplantation (3). Therefore, it is crucial to explore novel molecularly-targeted therapies and new prognostic factors for HCC patients (4)(5)(6). Very, recently, multiple personalized molecular subtypes of HCC have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that NRAV and AL031985.3 were highly expressed in HCC tissues, modified by m6A, and were associated with prognosis [ 49 , 50 ]. However, the mechanism by which m6A modifies these two lncRNAs remains unclear.…”
Section: Discussionmentioning
confidence: 99%